1996
DOI: 10.1109/72.478392
|View full text |Cite
|
Sign up to set email alerts
|

A review of Bayesian neural networks with an application to near infrared spectroscopy

Abstract: MacKay's (1992) Bayesian framework for backpropagation is a practical and powerful means to improve the generalization ability of neural networks. It is based on a Gaussian approximation to the posterior weight distribution. The framework is extended, reviewed, and demonstrated in a pedagogical way. The notation is simplified using the ordinary weight decay parameter, and a detailed and explicit procedure for adjusting several weight decay parameters is given. Bayesian backprop is applied in the prediction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(114 citation statements)
references
References 15 publications
0
114
0
Order By: Relevance
“…, N k . The benefit of translating cost function C (3) into C * (6) is that Bayes' rule (used to calculate the posterior) automatically embodies Occam's razor [19], and that minimizing C * , thus, leads to the simplest setting of ψ that is still warranted by the data D. In [19] and [24], it is shown that the maximum likelihood estimates for α and β can be expressed as follows:…”
Section: ) Bayesian-regulated Levenberg Marquardt (Lmbr)mentioning
confidence: 99%
See 1 more Smart Citation
“…, N k . The benefit of translating cost function C (3) into C * (6) is that Bayes' rule (used to calculate the posterior) automatically embodies Occam's razor [19], and that minimizing C * , thus, leads to the simplest setting of ψ that is still warranted by the data D. In [19] and [24], it is shown that the maximum likelihood estimates for α and β can be expressed as follows:…”
Section: ) Bayesian-regulated Levenberg Marquardt (Lmbr)mentioning
confidence: 99%
“…At each time period p > k for which no realized travel time d k of vehicles departing at k is available, the censored error (24) provides an incremental estimate of the model prediction error. Letting…”
Section: ) Online-delayed Ekf Algorithmmentioning
confidence: 99%
“…Bayesian back-propagation was initially introduced by MacKay [47][48], based on a Gaussian approximation to the posterior distribution of parameters. Previous study has shown that the Bayesian approach to parameter estimation typically attains more robust and accurate ANN models [49].…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…The wide acceptance of these linear methods is largely due to the inherent linearity between the analyte properties and spectral absorbance as stated in the Beer-Lambert's law [4]. However non-linear calibration methods have also been proposed for practical problems where the linearity does not hold, including neural networks [5], support vector machine and its variants [6,7].…”
Section: Introductionmentioning
confidence: 99%